Analysis of fatal unintentional drowning in Australia 2008-2020: implications for the Australian Water Safety Strategy - Amy E. Peden; Justin‐Paul Scarr; Alison J. Mahony (Elsevier, 2021)
Abstract Objective: To examine temporal trends in drowning in Australia against targets set in the Australian Water Safety Strategy (AWSS) 2008-2020 and to inform the development of the next iteration of the Strategy. Methods: A national analysis of unintentional fatal drowning rates per 100,000 population over 16 years (2004/05-2019/20) was conducted. Baseline rates (three‐year average 2004/05-2006/07) were compared to the current three‐year average (2017/18-2019/20) by sex, age group, drowning location and jurisdiction. Results: The overall rate of unintentional fatal drowning during the period decreased by 28%. Substantial reductions were observed in children 0-4 years (−63%) and 5-14 years (−56%). Progress has been less pronounced among people aged 75 years and over (−11%) and 15-24‐year‐olds (−14%). All locations and jurisdictions recorded reductions, aside from rocks (+46%). Conclusions: Although the strategy fell short of its aspirational target of a 50% reduction in drowning by the year 2020, this target was exceeded in key age groups, including children. Implications for public health: The AWSS is a powerful tool to align drowning prevention sector actions to agreed objectives. Forthcoming strategies must take into consideration demographic and social change, areas where limited progress has been made and the latest evidence to guide future priorities.